Epidemiological, clinical, haemato-biochemical and therapeutic evaluation of canine trypanosomosis in Mumbai - LAVANYA, K V; GUDEWAR, JAGDISH G; PEDNEKAR, RIDDHI P; GATNE, MUKULESH L (The Indian Journal of Animal Sciences, 2016)
Evaluation of 20 confirmed clinical cases of canine trypanosomosis caused by Trypanosoma evansi in Mumbai from June 2012 to May 2013 was done to compile the basic information on parasitological, epidemiological, clinical, clinico-pathological and chemotherapeutic aspects. The disease was predominantly found in the localities having substantial equine and bovine population thus underlining the potential source for canine cases. Molecular analysis of few representative samples also confirmed the ability of the organisms to crossover from one species to other species of host. The disease was characterized by clinical signs such as depression, anorexia, anaemia, fever, splenomegaly, hepatomegaly and oedema of legs and paraclinical findings such as low levels of TEC, Hb and PCV indicating anaemic trend, elevated levels of alkaline phosphatase, AST, ALT and hyperglobulinaemia associated with reversing of albumin: globulin ratio. Hypoglycaemic trend noted in the study was found positively correlated with intensity of parasitaemia. Blood glucose levels were inversely related to degree of parasitaemia. The chemotherapeutic options, diminazeneaceturate and antrycideprosalt although cleared parasitaemia but failed to provide complete recovery, as 50% of cases eventually died in spite of specific chemotherapy suggesting some secondary involvement in the disease entity.